Vaccination post-allogeneic hematopoietic stem cell transplantation: what is feasible? - Anne Conrad; Vincent Alcazer; Florent Valour; Florence Ader (Taylor & Francis Group, 2018)
Introduction: Allogeneic hematopoietic stem cell transplantation (HSCT) is a major curative treatment option for malignant and non-malignant hematological diseases, but is associated with an increased risk for infections, of which some are preventable by vaccination. Vaccination guidelines recommend repeated doses of most inactivated vaccines to achieve long-lasting immune responses. However, the efficacy of immunization is often hampered by graft-versus-host disease or severe opportunistic infections. Areas covered: This review summarizes the vaccine recommendations for adult allogeneic HSCT recipients and discusses the challenges and future directions regarding vaccine immunization in these patients. Expert commentary: Vaccination is a well-tolerated therapeutic intervention to prevent infections after allogeneic HSCT. Allogeneic HSCT recipients could benefit from experience regarding vaccine efficacy capitalized through specific data registries. An individualized immunization approach, modulating inception and intensity of vaccination schedule according to transplant characteristics, transplant-related complications and immune recovery status, might help to improve vaccine efficacy in this specific population. Identification of surrogate markers of the immune status and of vaccine efficacy, beyond antibody testing, as well as development of new vaccines are exciting fields of future research.